Faktor-faktor yang mempengaruhi Kinerja Auditor: Profesionalisme, Kompetensi Auditor dan Independensi Auditor - Karennia Junisa; Cris Kuntadi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Good audit performance will enable an accounting firm to achieve its goals and meet the financial reporting needs of stakeholders. Auditors must be experts in order to maintain the trust of clients and other users of audit financial reports. Auditor training improves the auditor's ability to carry out their work during the audit process. The central questions of this article are: (1) Does the auditor's ability, auditor professionalism, and auditor independence have an impact on performance. (2) Further review of previous articles, where consistency is still found. It is hoped that this research will contribute new thinking to the development of audit theory by reviewing aspects of auditor independence, professionalism and competence in the context of their performance. The purpose of writing this article is to establish a hypothesis about the influence between variables in further research. The findings of this literature review article are: 1) Auditor competency influences auditor performance; 2) Professionalism influences auditor performance; 3) Auditor independence influences auditor performance. Keywords: auditor performance, professionalism, auditor competence and auditor independence.